The Utilization of the Falou English Application for Speaking Development among University Students - Nisa Aldira Lubis,; Ernita Daulay, (Edumaspul: Jurnal Pendidikan, 2026)
This study explores the effectiveness of the Falou English application in enhancing the speaking skills of seventh-semester English Department students. Using a qualitative approach through questionnaires and interviews, the research investigates how students’ experiences with the app influence their speaking fluency, confidence, and academic communication. The findings show that students perceive the app as a helpful and engaging tool, providing interactive features and real-time feedback that support consistent and confident speaking practice. Despite its benefits, students also encountered several challenges, including technical issues, limited content access, and cultural or linguistic mismatches. These obstacles, however, did not diminish their overall positive perception of the app’s impact on speaking development. The study concludes that the Falou English application holds strong potential as a complementary tool for speaking instruction in higher education, contributing meaningfully to learner engagement, motivation, and communicative competence.